Analisis Kesalahan Siswa dalam Menyelesaikan Soal Sistem Persamaan Linear Dua Variabel (SPLDV) - Agnes Meilina; Hidayat Hidayat; Saiful Bahri; Asnarni Lubis (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2026)
This study aims to describe the types of errors and the factors causing errors made by students in solving System of Linear Equations in Two Variables (SLETV) problems based on Newman’s Error Analysis. This research is a descriptive qualitative study with the subjects being students of class IX-10 at SMP Negeri 1 Percut Sei Tuan in the 2025/2026 academic year. The data were collected through diagnostic tests, questionnaires, and interviews. The data analysis technique was carried out by identifying students' errors based on the five stages of Newman, namely reading errors, comprehension errors, transformation errors, process skill errors, and encoding errors. The results showed that students made errors at all stages of Newman’s procedure, with the dominant errors occurring at the transformation and process skill stages. These errors include students’ inability to understand the meaning of the problems, transform word problems into mathematical models, and carry out calculation procedures accurately. The factors causing students’ errors include low conceptual understanding, lack of procedural skills, lack of accuracy in answering questions, ineffective study habits, and low student attitudes toward mathematics. Based on the findings, it can be concluded that error analysis using Newman’s procedure is able to systematically identify the location of students’ errors in solving SLETV problems. Therefore, it is expected that teachers can use the results of this analysis as a basis for designing more effective learning strategies to minimize students’ errors and improve learning outcomes.